Prototype Mesin Pembuat Minuman Kopi Otomatis Terintegrasi Android - Masril, Mardhiah; Nasution, Ayu Lestiani; Zain, Ruri Hartika; Awal, Hasri; Hendrik, Billy (LPPM-ITEBA, 2025)
Coffee is one of the popular drinks. The Indonesian people drink coffee is a tradition to celebrate togetherness values and strengthen ties of brotherhood between communities. Along with high mobility society, everything is demanded to be instant and efficient. Coffee drinkers can come from various professions, ages and social background. The automatic coffee maker designed to address people's needs for coffee with an efficient serving process. Input on this design are coffee, milk and sugar where these ingredients can be processed into several types drinks that can be chosen are based on coffee. Design and construction of a microcontroller and android based coffee making equipment devices used to support the system these include the Arduino Mega 2560 as a microcontroller, servo and DC motor as an actuator, DS18B20 sensor as a water temperature reader, solenoid valve to drain the flow, and LCD for displays the coffee selection menu. The payment medium used in this coffee drink making tool is QR-code as practical, easy and responsive transaction. This tool could be an alternative that can be implemented by coffee drinkers or enthusiasts can enjoy coffee at the bus stop instantly just by using their personal Android.